Juridic Review Of The Implementation Of The Principle Of Good Faith In Online Buying Transactions - Ismail Yusuf (Estudiante Law Journal, 2020)
This study discusses the juridical review of the application of the principle of good faith in online buying and selling transactions. The objectives of this research are; To find out how the juridical review of the application of the principle of good faith To find out what are the inhibiting factors for the application of the principle of good faith in online buying and selling transactions The method used in this research is empirical normative research, which means to analyze research based on library data and based on the state of variables, and the phenomena that occur when the research takes place and presents it as it is. The results of the study show that to realize the principle of good faith in online buying and selling transactions, the government has regulated it in Article 1338 of the Civil Code which reads "All agreements made in accordance with the law apply as law for those who make them. The obstacles in applying the principle of good faith in online buying and selling transactions are the internal factors consisting of the contents of the agreement that are not in accordance, the agreement factor where the agreed goods are drawn are not in accordance with what was sent, and the object of the agreement is not appropriate. The external factors are security in transactions, settlements outside the law, consumer knowledge, the last factor is space and time distance, data authenticity and finally the factor in the existence of goods.